In Vitro Activity of Cefepime against Multidrug-Resistant Gram-Negative Bacilli, Viridans Group Streptococci and Streptococcus pneumoniae from a Cross-Canada Surveillance Study - Donald E Low; Joyce de Azavedo; Canadian Bacterial Surveillance Network; Ross Davidson (Canadian Journal of Infectious Diseases)
OBJECTIVE: To determine the in vitro activity of cefepime against multidrug-resistant Gram-negative bacilli and Gram-positive cocci obtained from an ongoing cross-Canada surveillance study.